Modeling study of reactive species formation from C1–C3 alkanes in an HCCI engine. Issue 6 (2nd November 2019) - Saylam, Ahmad; Atakan, Burak; Kaiser, Sebastian
Abstract : The production of oxygenated hydrocarbons, hydrogen peroxide, and ethylene by low and intermediate temperature reactions of C1 –C3 alkanes in a homogeneous charge compression ignition (HCCI) in an internal combustion engine was explored via single-zone modeling. For lean equivalence ratios, the main operating parameters were successively optimised with respect to intermediate species yield. A combination of 9–13 for compression ratio, 400 rpm for engine speed, and 0.05–0.25 for equivalence ratio was found for fixed intake temperature and pressure of 400 K and 1 bar, respectively. The optimum was sharply delineated in compression ratio, and widest in equivalence ratio. For these optimal parameters, 5–13.3% of the methane fuel was converted to formaldehyde and 1.6–3.4% to hydrogen peroxide, while more than 1% ethylene yield was found for ethane, and somewhat less for propane over that range. At this optimum, adding reactive species to methane as a fuel did not significantly improve yields, nor did varying intake temperature off the chosen 400 K, indicating that in fact the parameters combination is at least near-optimal. Operating conditions of an In-situ production unit of hydrogen peroxide and formaldehyde from methane partial oxidation have been explored to feed highly-efficient combustion and/or easy accessible/stabilised operating conditions of HCCI engine fuelled by low reactive fuel, the methane/natural gas.